Pemahaman Siswa Kelas IV SD dalam Memahami Konsep Pecahan Berdasarkan Angket - Aisyah Fitriani; Lina Permai Sahra; Suci Puteri Maulia; Muhammad Fendrik; Cici Oktaviani (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aimed to analyze the level of understanding of fraction concepts among fourth-grade students at SDIT Al Hidayah Pekanbaru and to identify effective learning strategies. Mathematics, particularly the concept of fractions, often poses a significant challenge at the primary education level. The research employed a descriptive quantitative approach, with primary data collected through the distribution of a questionnaire to 30 students. This questionnaire was designed to measure the students' mastery level of basic concepts, operations, and application of fractions.The findings indicate that the students' level of understanding of fraction concepts is in the very good category. This is evidenced by the questionnaire data, where 63.33% of respondents selected the "Strongly Agree" category and 25.71% selected "Agree," resulting in a cumulative total of 89.04% positive responses. This strong positive dominance suggests that the majority of students have mastered the fundamental concepts and can apply them. The results support the idea that contextual, interactive teaching methods, coupled with the use of manipulative media (as also suggested by relevant studies), are highly effective in facilitating students' deep conceptual understanding. The main conclusion is that implementing learning approaches oriented toward real-world contexts, combined with the use of instructional media, significantly improves student comprehension of fraction material. These findings are expected to serve as a valuable reference for teachers and stakeholders in developing more innovative and effective teaching methods in Primary Schools.